Modos de ser do trabalho para o movimento social e as políticas públicas de educação do campo - Silva, André Luiz Batista da (2018)
The present research had as general objective to understand the ways of being of the Work and of the Field Education - as well as its determinants and contradictions - in the contexts of the Social Movement of the Field Education and the Public Educational Policies for the people of the field. For that, the national documents of the Social Movement of the Field Education - ENERAs, CNECs and FONECs - and the documents of public policies produced within the scope of the Brazilian State from 1998 to 2016, expressed in legislations, Resolutions of the National Council of Education and programs of the Federal Government - PRONERA, PRONATEC, PROJOVEM - Field, PRONATEC - Field. The specific objectives of the research were: 1 - to analyze the presence and place of work in the conception and production of knowledge about Field Education; 2 - to analyze the way of being, the place and the presence of the work in the documents of the Social Movement of the Field Education; 3 - to analyze the way of being, the place and the presence of the work in the documents of public educational policies for the field; 4 - to analyze the way of being of the Field Education for the Social Movement of the Field Education and for the public educational policies for the field. Methodologically, the research was based on historical materialism and, procedurally, used bibliographical and documentary analysis. The work was treated theoretically from its founding character of human and proto-modern sociality of human action in general-praxis. In addition to the founding character (LUKÁCS, 2012, 2014), the work was treated in two ways: the mode of being exploited and unexplored (MARX, 1978, 2014). The place of work in the concept and in the production of knowledge in Field Education was sequentially analyzed. Afterwards, the ways of being of the work and of the Education of the Field for the Social Movement of the Field Education were analyzed and, finally, the ways of being of the Work and of the Field Education for the Public Educational Policies for the people of the field. As a result of research it is evident that in the scope of the public policies focused on the education of the peoples of the countryside and of professional and technical training, the work presents itself in the way of being exploited / alienated, differently from the way in which the work presents itself in the documents of the Social Movement of the Field Education as non-exploited / emancipatory work. It was also evidenced that in the public policies for Field Education and Professional and Technical training in which there was greater participation of the Social Movement of Field Education in the process of elaboration and management the way of being of the work presented itself as not – exploited – PRONERA -, unlike public policies in which the Social Movement had no participation - PRONATEC. It was also observed that the determinants of the different ways of being in which the work is presented in the documents of public policies and in the documents of the Social Movement of the Field Education are constituted of the class struggle and the political praxis.